2022
DOI: 10.1186/s12885-022-10156-8
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of the protein kinase inhibitor 1-(β-D-2′-deoxyribofuranosyl)-4,5,6,7-tetrabromo- 1H-benzimidazole in breast cancer cell lines

Abstract: Background The protein kinases CK2 and PIM-1 are involved in cell proliferation and survival, the cell cycle, and drug resistance, and they are found overexpressed in virtually all types of human cancer, including breast cancer. In this study, we investigated the antitumor activity of a deoxynucleoside derivative, the protein kinase inhibitor compound 1-(β-D-2′-deoxyribofuranosyl)-4,5,6,7-tetrabromo-1H-benzimidazole (K164, also termed TDB), inter alia CK2 and PIM-1, on breast cancer cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Moreover, it was demonstrated that the inactivation of BAD by PIM-1-mediated phosphorylation of Ser112 can affect BCL-2, an apoptotic cell death suppressor, which consequently leads to cell survival [57]. A similarly increased level of phospho-BAD (Ser112) was observed in TNBC MDA-MB-231 cells after treatment with a dual CK2/PIM-1 inhibitor, 1-(β-D-2 -deoxyribofuranosyl)-4,5,6,7tetrabromo-1H-benzimidazole, named K164 (TDB) [37]. Interestingly, the same inhibitor reduced the catalytic activity of both CK2 and PIM-1 kinases, as manifested by decreased phosphorylated levels of Akt and BAD in K-562 cells, and induced apoptosis in this cell line [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was demonstrated that the inactivation of BAD by PIM-1-mediated phosphorylation of Ser112 can affect BCL-2, an apoptotic cell death suppressor, which consequently leads to cell survival [57]. A similarly increased level of phospho-BAD (Ser112) was observed in TNBC MDA-MB-231 cells after treatment with a dual CK2/PIM-1 inhibitor, 1-(β-D-2 -deoxyribofuranosyl)-4,5,6,7tetrabromo-1H-benzimidazole, named K164 (TDB) [37]. Interestingly, the same inhibitor reduced the catalytic activity of both CK2 and PIM-1 kinases, as manifested by decreased phosphorylated levels of Akt and BAD in K-562 cells, and induced apoptosis in this cell line [36].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that the use of dual inhibitors of CK2 and PIM-1 is beneficial for the reduction in cell proliferation and induction of apoptosis in cancer cell lines, i.e., cervical cancer (HeLa) and chronic myeloid leukemia (CML) [ 35 , 36 ]. The most recent studies demonstrated that inhibitor K164 is a promising compound that can be considered a potential active agent in targeted therapy in selected types of breast cancer [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research that has been believed to have been conducted suggests that the action may also be displayed by chemicals such as thiadiazol, tetrazole, triazines, and imidazole. 43…”
Section: Antitumor Activitymentioning
confidence: 99%